2009
DOI: 10.1007/s13199-009-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of arbuscular mycorrhizae and dark septate endophytic fungi in an undisturbed and a disturbed site of an arid ecosystem

Abstract: Effect of disturbance on root colonization and vertical distribution of arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE) was investigated at two adjacent sites of Lal Suhanra Biosphere Reserve, Pakistan. Disturbance clearly affected AMF and DSE colonization, vertical distribution of AMF and plant community structure. Mean colonization of AMF and DSE was slightly less at the disturbed site. Average spore densities, diversity and richness of AMF and DSE were higher at the undisturbed site. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Chaudhry et al (2009) also reported higher spore numbers (averaging 111 spores per 100 g soil) in grasses from undisturbed and disturbed sites of an arid ecosystem in Pakistan. Gai et al (2006) reported a spore number of 10 to 300 spores per 100 g soil from grasses of southern Tibet.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Chaudhry et al (2009) also reported higher spore numbers (averaging 111 spores per 100 g soil) in grasses from undisturbed and disturbed sites of an arid ecosystem in Pakistan. Gai et al (2006) reported a spore number of 10 to 300 spores per 100 g soil from grasses of southern Tibet.…”
Section: Discussionmentioning
confidence: 83%
“…It has been predicted that taxa belonging to more than 80% of the plant families are mycorrhizal. Inspite of its large family size, less than 500 species of grasses have been examined for their mycorrhizal status (Ragupathy and Mahadevan 1993;Muthukumar and Udaiyan 2000;Wang and Qiu 2006;Chaudhry et al 2005Chaudhry et al , 2006Chaudhry et al , 2009Fracchia et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined that the DSE-colonized plants also had AM fungal associations, as others have found (Sengupta et al 1989;Muthukumar et al 2006;Muthukumar & Tamilselvi 2010). Chaudhary et al (2009) contended that the simultaneous occurrence of DSE and AM fungi indicates the dynamic nature of the endophyte community in natural ecosystems. During unfavorable conditions, DSE fungi can function as mutualists by taking up water and nutrients from the soil and translocating them to plant roots (Mandyam & Jumpponen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Además, se sugiere que ocasionalmente los DSE reemplazan a los HMA y a los HECM en ecosistemas árticos y alpinos debido a las condiciones ambientales extremas, ya que estos hongos se encuentran de manera constante (Redman et al, 2002;Chaudhry et al, 2009;Upson et al, 2009b;Pan et al, 2013). Los DSE Leptodontidium sp., L. orchidicola y Phialocephala fortinii han sido registrados como colonizadores de orquídeas como Calypso bulbosa (L.) Oakes, Coeloglossum viride (L.) Hartm., Corallorhiza maculate Raf.…”
Section: Interacciones De Los Hongos Endófi Tos Septados Obscuros Conunclassified